Istisyhād Ibn Taimīyah fi al Nahwi wa al Sarfi wa al Lughah - Rizki Gumilar (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2022)
Sampling of Ibn Taymiyya in grammar, morphology and language According to Imam adz-Dzahabi, Ibnu Taimiyyah is a figure who mastered the language of both his ushul and his furu', both his ta'lil and his ikhtilaf, and he studied the kitab Sibawaih with Ibn Abd al-Qawy in a few days and was able to master it. well. In this research, we will discuss how Ibn Taimiyyah's method of using istisyhad and what types of texts he used to defend his hujjah in the problems of nahwu, shorof, and lughah. Researcher see the analysis that is in accordance with this research is descriptive analysis, starting from data collection, assessment, to presenting the results.